Between Livelihood and Dependency: Trends, Drivers, and Socio-Economic Implications of Labor Migration from Besisahar Municipality to the Gulf Countries - Timalsena, Nisha (NPRC Journal of Multidisciplinary Research, 2026)
Background: Labour migration to Gulf Cooperation Council (GCC) countries has become a primary livelihood strategy for many households in Nepal. While national-level data on remittances is available, there is a significant lack of localized studies examining the specific drivers and socio-economic consequences of this migration pattern.Objectives: This study aims to explore the socio-demographic profile, causal factors, and socio-economic impacts of labour migration from Besisahar Municipality, Lamjung, to GCC countries.Methods: A descriptive mixed-method design was employed. Data were collected from 30 migrant households using surveys, semi-structured interviews, and a focus group discussion. Participants were selected using a purposive sampling method to ensure they had firsthand experience with migration to the GCC. The data collection period was from January to March 2025. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis.Results: The majority of migrants were working-class adults aged 20-40 years (66.6%) and had low to moderate education levels (66.6% with Grade 10 or below). The largest shares of migrants were employed in the construction industry (33.3%), manufacturing (26.7%), and domestic work (20.0%). Employment scarcity at home was identified as the main driver for migration (40.0%), rather than a simple desire for employment. Perceptions regarding the effectiveness of migrant work were moderately positive (mean: 4.13/5.00). However, there was a neutral/mixed feeling regarding the overall increase in migration (mean: 3.00/5.00).Conclusion: Migration to GCC countries is framed as a structurally determined coping mechanism for economic survival rather than a purely voluntary choice. While it provides immediate economic relief, it creates a long-term dependency on remittances for the household unit.